2003
DOI: 10.1590/s0037-86822003000300014
|View full text |Cite
|
Sign up to set email alerts
|

Presença extra-intestinal de cistos unizóicos de Isospora belli em paciente com SIDA: relato de caso

Abstract: This report describes the presence of Isospora belli unizoic cysts in mesenteric lymph nodes and of gametocytes in the gallbladder epitelium of a 26 year-old Brazilian male patient with Acquired Immune Deficiency Syndrome. This patient had received treatment for several times with sulfamethoxazole-trimethoprim. It is discussed the significance of I. belli tissue cysts as possible foci of resistance of the parasite and their association with the infection relapse even post-treatment with anticoccidian medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
2
0
5
Order By: Relevance
“…O quadro pode ser de diarreia profusa, com número superior a oito evacuações diárias. Pode ocorrer perda de peso, dor abdominal em cólica, vômito e desidratação, necessitando, em muitos casos, de hospitalização (FRENKEL et al, 2003).…”
Section: Aspectos Clínicosunclassified
“…O quadro pode ser de diarreia profusa, com número superior a oito evacuações diárias. Pode ocorrer perda de peso, dor abdominal em cólica, vômito e desidratação, necessitando, em muitos casos, de hospitalização (FRENKEL et al, 2003).…”
Section: Aspectos Clínicosunclassified
“…C. belli shed in human feces forms unizoic cysts in extra-intestinal tissues of humans, the definitive host (Lindsay et al 1997;Frenkel et al 2003); their intermediate host has not been identified. These species were described originally in the genus Isospora, in the belief that they were monoxenous organisms.…”
Section: Cystoisosporamentioning
confidence: 99%
“…In patients with the acquired immunodeficiency syndrome (AIDS) it has been described as another opportunistic agent that can cause chronic diarrhoea, acalculous cholecystitis and cholangiopathy (Benator et al 1994; Zenta and Topazian, 2009). Reports of disseminated cystoisosporosis with unizoite tissue cysts in the lamina propria of the intestines, lymph nodes, liver and spleen in patients with AIDS have been published (Comin and Santucci, 1994; Restrepo et al 1987; Michiels et al 1994; Velasquez et al 2001; Frenkel et al 2003). The Cystoisospora felis species infects cats and several hosts (Dubey and Frenkel, 1972; Costa and Lopes, 1998; Melo et al 2003).…”
Section: Introductionmentioning
confidence: 99%